1983
DOI: 10.1093/ajcp/80.3.369
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment of Laboratory Tests in the Diagnosis of Acute Appendicitis

Abstract: A comparison of laboratory tests was undertaken in 106 patients admitted to the emergency room with the tentative diagnosis of acute appendicitis and who subsequently underwent appendectomy. The tests examined included the total white blood cell count, manual differential count, cytochemical differential count, and C-reactive protein. The sensitivity, specificity, efficiency, and predictive value of these tests in the diagnosis of acute appendicitis were calculated. The cytochemically determined neutrophil cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(26 citation statements)
references
References 0 publications
2
24
0
Order By: Relevance
“…Several reports suggest that an elevated leucocyte count is usually the earliest laboratory test to indicate appendiceal inflammation, and most of the patients with acute appendicitis present with leukocytosis. [6][7][8][9][11][12][13]15 The neutrophil percentage has also been thought to be of value, as a relative neutrophilia is often associated with bacterial infection. 9 In this study, the sensitivity of leucocyte count in diagnosing acute appendicitis was 85.8%, which is in accordance with other studies that reported a sensitivity of 82-96%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several reports suggest that an elevated leucocyte count is usually the earliest laboratory test to indicate appendiceal inflammation, and most of the patients with acute appendicitis present with leukocytosis. [6][7][8][9][11][12][13]15 The neutrophil percentage has also been thought to be of value, as a relative neutrophilia is often associated with bacterial infection. 9 In this study, the sensitivity of leucocyte count in diagnosing acute appendicitis was 85.8%, which is in accordance with other studies that reported a sensitivity of 82-96%.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with acute appendicitis often present with a raised leucocyte count, but owing to a considerable overlap with other inflammatory processes mimicking acute appendicitis, the diagnostic value of the leucocyte count remains controversial. [3][4][5][6][7][8][9] Additional laboratory tests that aid in the diagnosis of acute appendicitis include the C-reactive protein (CRP), which is synthesized by hepatocytes during acute-phase response to a variety of infectious or inflammatory processes. Many reports have investigated the value of CRP in improving the diagnosis of acute appendicitis, but with conflicting results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The appendicitis data set is from a published study on the assessment of 8 laboratory tests to confirm the diagnosis of appendicitis (26). Following surgery, only 85 out of 106 patients were confirmed by biopsy to have had appendicitis.…”
Section: Methodsmentioning
confidence: 99%
“…Marchand et al pointed out that the positive predictive value (PPV) and negative predictive value (NPV) of an elevated WBC in AA are 92 and 50 percent, respectively [16]. Traditionally, patients are expected to have WBC counts between 12,000 and 18,000 per mm 3 with AA and 15,000 to 25,000 with perforated appendicitis.…”
Section: Laboratory Adjuncts In the Diagnosis Of Acute Appendicitismentioning
confidence: 99%